Phenotypic extremes in liveborn monozygotic twins with mosaic Edwards syndrome. (11th November 2015) - Bussmann, Neidin; Cunningham, Katie; Green, Andrew; Ryan, C Anthony
Abstract : Mosaic trisomy 18 (Edwards syndrome) in monozygotic diamniotic liveborn twins is rare. We describe such a case involving preterm male infants. Although both infants had a low percentage of trisomy 18 cells in peripheral blood leucocytes, their varied phenotypic presentation of mosaic trisomy 18 resulted in one twin surviving, with the other twin's demise at 1 month of age. Despite the presence of trisomy 18 in peripheral leucocytes, further analysis of a buccal smear and skin biopsy of the surviving twin did not show evidence of trisomy 18. Establishing such diagnoses in a timely manner is imperative for the child, parents and clinicians. The clinical course of these twins reflects the unpredictable prognosis associated with the diagnosis of mosaic trisomy 18, and emphasises the challenges that can be encountered when counselling parents.